Filtering by Race and Education in the U.S. Manufacturing Sector: Constant-Ratio Elasticity of Substitution Evidence - Dick, Daniel T.; Medoff, Marshall H. (The Review of Economics and Statistics, 1976)
Daniel T. Dick, Marshall H. Medoff, Filtering by Race and Education in the U.S. Manufacturing Sector: Constant-Ratio Elasticity of Substitution Evidence, The Review of Economics and Statistics, Vol. 58, No. 2 (May, 1976), pp. 148-155